Catching fire - Collins, Suzanne (New York : Scholastic, 2009)
By winning the annual Hunger games, District 12 tributes Katniss Everdeen and Peeta Mellark have secures a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.
The second book of The Hunger Games.Strictly for G7 students and above level of age use.
Keywords: Insurgency -- Fiction; Survival -- Fiction; Interpersonal relations -- Fiction